Contribution of soluble organic matter to hydrocarbon generation in saline lacustrine source rocks: Evidence from thermal simulation experiments - Xing, Lantian; Xu, Li (Frontiers in Earth Science, 2023)
Soluble organic matter generally exists in the source rocks of saline lacustrine basins. In this paper, we quantified the contribution of soluble organic matter to hydrocarbon generation on the basis of thermal simulation experiments using a saline lacustrine source rock from the Qaidam Basin. Our results show that the yields of gaseous and liquid hydrocarbons in the thermal simulation products are greatly improved in the presence of soluble organic matter. As a comparison, the maximum yields of gaseous and liquid hydrocarbons in series C (without soluble organic matter) were 270 and 329.78 mg/gTOC, respectively, while in series A (with soluble organic matter) they were 364 and 602.98 mg/gTOC, respectively. The proportion of isoprenoids and n-alkanes in the products also increased from approximately 3% to 40%. Meanwhile, the presence of soluble organic matter reduced the temperature corresponding to the hydrocarbon generation peak from 375 to 250 °C. Moreover, the presence of soluble organic matter also had a remarkable change on the stable carbon isotope composition of methane, resulting in more 12C enrichment with a range of 2.24‰‒5.25‰. The combined evidence indicates that soluble organic matter can promote the formation of immature‒low maturity oil in source rocks.